ANCIENT SCHWANNOMA MASQUERADING AS CAROTID BODY TUMOR-A RARE CASE REPORT WITH REVIEW OF LITERATURE: Case Report - Gowthami N,; Nishat Afroz,; Murad Ahmed,; Midhunraj R, (International Journal of Histopathological Interpretation, 2023)
The most common tumor at carotid artery bifurcation is a carotid body tumor causing widening of bifurcation, usually seen on conventional arteriography that can also be produced by schwannoma of the cervical sympathetic chain. Ancient schwannoma is the uncommon variety of schwannoma, a benign tumor that arises from the nerve sheath. It usually arises from any nerve except the optic and olfactory. Here we present a rare case of a male in his early 50s with lateral neck swelling diagnosed radiologically and excised as a carotid body tumor diagnosed as ancient schwannoma on histopathological examination. Although quite rare, cervical sympathetic chain schwannoma should be considered a differential diagnosis for tumors at the carotid bifurcation. Insight into morphological features of ancient schwannoma avoids misdiagnosis as a malignant nerve sheath tumor.